Short and long-term efficacy and phytotoxicity of phosphine against Rhynchophorus ferrugineus in live Phoenix canariensis palms - Dembilio, Óscar; Jaques, Josep A. (2017)
The red palm weevil, Rhynchophorus ferrugineus, is a palm borer native to South Asia which has spread mainly due to the unintended movement of infested planting material. As a result, this species has become the most destructive palm pest in the world. The difficulty of detecting the early stages of infestation due to its cryptic life cycle has led many countries to implement, strict pre- and post-entry quarantine regulations to prevent further spread. However, there are no quarantine protocols to ensure that palm material for planting is free of R. ferrugineus. The aim of this study has been to determine the efficacy of aluminium phosphide as a safe quarantine treatment against different stages of R. ferrugineus and the possible phytotoxic effects on live Phoenix canariensis palms. Our results confirm that a dose of 1.14 g/m(3) for 2 days is enough to kill all stages of R. ferrugineus in live palms with no phytotoxic effects on treated palms for up to one year after the treatment. This procedure, which could be easily applied in sealed containers used for palm trade, could drastically reduce risks associated to palm movement worldwide.